Bone status in cystic fibrosis. Issue 6 (1st June 2001) - Sood, M; Hambleton, G; Super, M; Fraser, W D; Adams, J E; Mughal, M Z
Abstract : AIM: To investigate bone mineral status of children with cystic fibrosis (CF). METHODS: In 29 children with CF and 49 matched controls, bone mineral content (BMC), projected bone area (BA), and areal bone mineral density (BMD) of the whole body, total hip, and lumbar spine (L1–L4) were measured using dual energy x ray absorptiometry. The BMC values at each site were adjusted for BA, height, and weight. At the lumbar spine, the bone mineral apparent density (BMAD) was calculated by dividing the BMC by the estimated volume, derived from BA. Vertebral (T12–L3) trabecular bone mineral density (vTBMD) was measured using quantitative computed tomography in children with CF. Calcaneal broadband ultrasound attenuation (BUA) was measured in CF patients and controls using quantitative ultrasound. The disease severity of CF children was evaluated by the Shwachman–Kulczycki (SK) score. RESULTS: The mean BUA, whole body and regional BA, adjusted BMC, and areal BMD of children with CF were not different from those of controls. The mean BMAD of the lumbar spine was reduced in CF patients compared with controls, whereas the mean vTBMD standard deviation scores were significantly higher in CF patients. The median SK score of the CF group was 81 (range 42–100), indicating that as a group our CF patient population had relatively mild disease. CONCLUSION: The normal vertebral BMC, decreased BMAD, and higher vTBMD suggests that the vertebral cortical thickness or density might be reduced in CF subjects. The overall bone mineral status of CF children with relatively mild disease was not different from size matched controls.